Physics projects for young scientists - Adams, Richard C. (Richard Crittenden); Goodwin, Peter, 1951- (New York : F. Watts, 2000)
Gives instructions for and explains the principles behind a variety of simple physics experiments.
Rev. ed. of: Physics projects for young scientists / Richard C. Adams and Peter H. Goodwin, c1991.
Includes bibliographical references (p. 120-121) and index.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Senior High School.
Young Adult
Keywords: Physics -- Experiments -- Juvenile literature; Physics -- Experiments -- Methodology -- Juvenile literature; Physics -- Experiments; Physics -- Experiments; Physics -- Experiments -- Methodology; Science -- Experiments